The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2006
DOI: 10.1007/s00422-005-0048-2
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Centering Effects in Body Orientation

Abstract: This study mathematically characterizes the results of DiZio and Lackner (Percept Psychphys 39(1): 39-46) on the perception of self-orientation during circular vection induced by an optokinetic stimulus. Using the hypothesis of perceptual centering, it is shown that five basic centering transformations can logically account for the full range of illusions reported by the subjects. All five of these transformations center the perceived orientations of body components, the rotating disk, and gravity : two align … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 11 publications
(43 reference statements)
0
8
0
Order By: Relevance
“…This experiment demonstrates a large response space of perceptions, and subsequent work has related the results to perceptual transformations. The perceptions can be explained mathematically by sequences of physiological perception transformations, which form a semigroup that mathematically characterizes the perceptual dynamics [27]. Each transformation takes an orientation to another orientation that is more centered, in the sense explained in the previous paragraph.…”
Section: Rotating Diskmentioning
confidence: 99%
“…This experiment demonstrates a large response space of perceptions, and subsequent work has related the results to perceptual transformations. The perceptions can be explained mathematically by sequences of physiological perception transformations, which form a semigroup that mathematically characterizes the perceptual dynamics [27]. Each transformation takes an orientation to another orientation that is more centered, in the sense explained in the previous paragraph.…”
Section: Rotating Diskmentioning
confidence: 99%
“…We argue that the illusory weight change in our study is related to this type of illusory self-acceleration. Consistent with this notion, Hanes ( 6 ) reported that when a subject views an optokinetic stimulus, his or her perception of inertial self-motion is often changed to accord with the perceived (in this case, actually sensed) visual motion (p. 252). However, it would also be interesting for future studies to compare and contrast the vection and perceived weight changes obtained using our constant velocity self-motion displays to those generated by displays simulating vertical self-accelerations.…”
Section: Discussionmentioning
confidence: 70%
“…It is likely therefore to be involved in the vection illusions caused by a tilted rotating disk (DiZio and Lackner 1986;Hanes 2006). Subjects experienced illusions of body position, including head tilt and gaze direction, which reoriented the rotating disk to a horizontal position (Fig.…”
Section: The Symmetry Group and Functions Of The Uvula-nodulusmentioning
confidence: 98%